Smart contracts: Uso da tecnologia blockchain para garantia da eficácia dos acordos celebrados (Revista Direito em Debate, 2023)
Blockchain and smart contracts have been presented as innovative solutions for a number of issues, in particular, for contracting and business models. Blockchain is a decentralized network in which registered information acquires immutability. This technology enabled the implementation of smart contracts, which despite the name, are not contracts themselves, but software capable of self-executing what was previously agreed between the parties, ensuring effectiveness of the agreements entered into, security and cost reduction. Both technologies have stood out for the numerous advantages they present, making it pertinent to reflect on the replacement of traditional contractual methods with the new technological scenario. Through extensive exploratory and descriptive research, we sought to identify the factors that trigger the nature of blockchain technology, making notes about the main characteristics found. The procedures used were bibliographic research, documentary research, and case study, aiming to examine the reflexes in contemporary society.